EVALUASI SISTEM PENGENDALIAN MANAJEMEN PADA PUSAT PENDAPATAN DAN PUSAT BIAYA UNTUK MENINGKATKAN KINERJA MANAJER PENJUALAN - Pratipta, Hesti (Akuntansi, 2015)
This study aims to find out the effect of the implementation of management control structure at the revenue center and cost center to the performance sales manager and the implementation of management control process at the revenue center and cost center to the performance sales manager. The population in this study were 100 respondents addressed to the sales, purchasing, were house, shipping, accounting and production. Data collection techniques using survey and direct observation method that is by providing a questionnaire o the object of research. Analysis of data using multiple linear regression method. The results of this study indicate that there is a positive and significant impact of management control structure to the performance sales manager, there is a positive and significant impact of management control process to the performance sales manager and there is a positive and significant impact of management control structure and management control process to the performance sales manager, both of these variables contribution of 20,5 percent. Keywords: management control system, revenue center, cost center, performance sales manager